Determinantes do risco soberano: o impacto de variáveis econômicas, políticas e sociais - Tiago Cancado Diniz (2011)
The analysis of the impact of economic, political and social variables in the classifications of sovereign risk made by the Standard & Poor's rating agency from 2005 to 2009 for 88 developed and developing countries was the object of this research. The use of different statistical techniques, in which stand Multiple Linear Regression, the General Model for Panel Data and the Panel with Fixed Effect on Countries and Periods, allowed to identify important aspects for explanation of sovereign rating. The results of this study confirm theoretical expectations that countries with lower inflation rates, reduced level of indebtedness in relation to the GDP, and where the governments are more effective in the elaboration and implementation of public politics tend to present better score of rating. Other factors that demonstrated significant influence in the evaluations of sovereign risk, for the sample analyzed, are the degree of economic development and the geographic localization of the countries. Developing countries or countries located in Latin America and Caribbean or in Africa presented lower scores than those gotten only with the economic, political and social variables analyzed. On the other hand, developed countries or countries located in Europe and North America presented greater scores than those gotten only with the economic, political and social variables. The absence of significant relation between the educational level, measured by variable HDI - Education and the sovereign risk was evidenced in all statistical techniques that were used. Similar effect was observed between the longevity factor, measured by variable HDI - Life expectancy and rating classification, since only in Panel with Fixed Effect on Countries the relation between this variables was significant. Analysis of subprime financial crisis effect (initiated in 2007) in the sovereign classifications was evidenced by the model of panel data with period fixed effect. A reactive position of the S&P agency was evidenced in relation to the crisis, since the dummy that captures the period effect presents positive signal from 2005 to 2007 and negative signal from 2008 to 2009.